STATUS GIZI, ANEMIA DAN PRODUKTIVITAS KERJA PADA TENAGA KERJA WANITA (STUDI: LITERATURE REVIEW) - Parmasari, Damairia Hayu (Indonesian Journal of Nutrition Science and Food, 2024)
Background: Work productivity is a crucial problem in the work environment. Productive human resources will produce quality products and services. Female workers as human resources who actively work cannot be separated from the problem of work productivity. Factors that can influence the work productivity of female workers are nutritional status and anemia. Nutritional status as an impact of food consumption and a woman's menstrual cycle which is at risk of causing anemia can affect the productivity of the female workforce. The aim of the research is to determine the relationship between nutritional status, anemia and work productivity of female workers. Research method: This research is a literature study in 5 research journals regarding nutritional status, anemia, and work productivity of female workers. Researchers examine the elements in the journal, namely title, location, research subject, and research results. The elements in these 5 journals are studied with other research and theories. Research Results: The five pieces of literature used showed that 2 pieces of literature showed a significant relationship between nutritional status and work productivity of female workers, and 1 piece of literature showed a relationship that was not significant. In addition, 2 pieces of literature show a significant relationship between anemia and work productivity in female workers. Conclusion: The literature shows a significant and insignificant relationship between nutritional status and anemia and work productivity in female workers. Key words: Nutritional status, anemia, work productivity.